HUBUNGAN ANTARA FAKTOR PEMBENTUK PERSEPSI DENGAN PERSEPSI PEMUDA DESA TERHADAP PEKERJAAN SUB SEKTOR PETERNAKAN - Rindea Wini Pertiwi; Suwarto Suwarto; Agung Wibowo (Universitas Sebelas Maret, 2016)
This research aims to analyze a relation between the factors with perception, and different perception of the swain who lived near and far away from central government.The basic research is descriptive analytical method. Research locations in the village ringin larik and lampar. Sampling methods used the cluster of sampling a multistage, total sample is 50. The data used is primary and secondary data. The analysis to know the relationship between the factors with perceptionis rankspearman, t test to test the significance of the rankspearman, u- mann-whitney to test different perceptions.The result showed: A factor shaping the perception towards revenue farm work is age, involvement of work, family environment, social environment primer, cosmopolitan. A factor shaping the perception thowards status of employment is involvement of work, family environment, social enivironment primer. A factor shaping the perception towards the location of employment is involvement of work, family environment, social environment primer, social environment secunder, economic environment, social culture. A factor shaping the perception towards the opportunity or develop a career is family environment, economic environment. A factor shaping the perception thowards retirement is non formal education, involvement of work, social culture. In general, the factors forming perception towards is involvement of work, family environment and social environment primer. Perception of the swain that lived away in good than the swain who lived near.